2020
DOI: 10.3390/molecules25133100
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Features and Metal Ions That Influence 10-23 DNAzyme Activity

Abstract: Deoxyribozymes (DNAzymes) with RNA hydrolysis activity have a tremendous potential as gene suppression agents for therapeutic applications. The most extensively studied representative is the 10-23 DNAzyme consisting of a catalytic loop and two substrate binding arms that can be designed to bind and cleave the RNA sequence of interest. The RNA substrate is cleaved between central purine and pyrimidine nucleotides. The activity of this DNAzyme in vitro is considerably higher than in vivo, which was sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 105 publications
0
15
0
Order By: Relevance
“…Additionally, DNA has been proposed to have arisen before a reverse transcriptase enzyme existed by chemical deoxygenation of ribonucleotides [ 3 ]. Similar functions of ribozymes have recently been attributed to desoxyribozymes, “DNAzymes”, which can cleave and join and show similar properties as RNA ribozymes [ 35 ].…”
Section: The Ancient Rna Worldmentioning
confidence: 88%
“…Additionally, DNA has been proposed to have arisen before a reverse transcriptase enzyme existed by chemical deoxygenation of ribonucleotides [ 3 ]. Similar functions of ribozymes have recently been attributed to desoxyribozymes, “DNAzymes”, which can cleave and join and show similar properties as RNA ribozymes [ 35 ].…”
Section: The Ancient Rna Worldmentioning
confidence: 88%
“…For instance, in the computational scan of siRNA molecules there are additional factors that can be taken into account, such as internal structure of the target RNA ( 36 ) and specific nucleotide composition ( 37 ), among others [reviewed in ( 38 )]. A specific feature of DNAzymes that can also be considered is the preference of certain purine:pyrimidine junctions over other combinations ( 18 , 28 ). We specifically focused here on those junctions reported to be the most efficient (GU and AU), but future models may incorporate other combinations to study the joint effect of purine:pyrimidine junctions and other features.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we focus on the ‘10–23’ DNAzyme, an RNA-cleaving molecule, consisting of a 15-nucleotide catalytic core flanked by substrate binding arms of variable length and sequence that confer specificity by interacting with target RNA via Watson–Crick base pairing interactions ( 16 ). These DNAzymes cleave RNA between an unpaired purine (A, G) and a paired pyrimidine (U, C) in the presence of a divalent cation, such as Mg 2+ , via a de-esterification reaction ( 17 , 18 ). This results in phosphodiester bond cleavage of the target and generation of two RNA fragments ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Metal ions are essential elements for the catalytic activity of most known DNAzymes and play key roles in the catalytic process ( McGhee et al, 2017 ; Rosenbach et al, 2020 ). We found that DNAzymes showed different cleavage activity rates in the presence of divalent metal ions ( Figures 3D – F ), which may have been related to the inherent phosphate affinities of the different metal ions ( Schnabl and Sigel, 2010 ).…”
Section: Discussionmentioning
confidence: 99%